2010
DOI: 10.1186/1748-5908-5-92
|View full text |Cite
|
Sign up to set email alerts
|

Using knowledge brokers to facilitate the uptake of pediatric measurement tools into clinical practice: a before-after intervention study

Abstract: BackgroundThe use of measurement tools is an essential part of good evidence-based practice; however, physiotherapists (PTs) are not always confident when selecting, administering, and interpreting these tools. The purpose of this study was to evaluate the impact of a multifaceted knowledge translation intervention, using PTs as knowledge brokers (KBs) to facilitate the use in clinical practice of four evidence-based measurement tools designed to evaluate and understand motor function in children with cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(194 citation statements)
references
References 34 publications
8
184
2
Order By: Relevance
“…While nine studies reported various provider characteristics such as age, gender, years of experience, work location, and caseload levels, one study reported only the professional discipline of the providers (33), and one study reported only 'mental health providers' without specifying any further provider characteristics (25). Four of the studies included some characteristics of the patients in whom the outcome measure was being applied to (25,28,32,34). Most often, these characteristics included age and diagnosis.…”
Section: Study Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…While nine studies reported various provider characteristics such as age, gender, years of experience, work location, and caseload levels, one study reported only the professional discipline of the providers (33), and one study reported only 'mental health providers' without specifying any further provider characteristics (25). Four of the studies included some characteristics of the patients in whom the outcome measure was being applied to (25,28,32,34). Most often, these characteristics included age and diagnosis.…”
Section: Study Descriptorsmentioning
confidence: 99%
“…There was one randomized controlled trial (31), two controlled before and after studies (29,35) , seven before and after studies (1,25,27,28,30,33,34), and one retrospective cohort study (32). Nine of the eleven studies had an overall quality rating of weak.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Review of abstracts and/ or titles disqualified a further 1,496 papers that were deemed not potentially relevant to the review objective. We then obtained the remaining 17 papers for detailed review, which resulted in a total of four studies [37][38][39][40] meeting the eligibility criteria (see Figure 1). Two of these studies used mixed methods, one used qualitative methodology, and one used case presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent quantitative research in healthcare has shown mixed results for short-term, knowledge management-based intermediary interventions (Dobbins et al, 2009;Russell, 2010). It seems unlikely that a consistent evidence base on the effectiveness of intermediary interventions will emerge, given the breadth of the concept, its context-dependent and contingent nature, and the complexity of the social processes involved-all of which will confound experimental research approaches.…”
Section: Intermediary Work and 'Knowledge Brokering'mentioning
confidence: 99%